Pendampingan Pelaporan SPT Tahunan 1770 Wajib Pajak Usahawan Melalui E-Form Pada KPP Pratama Bogor - Azhar, Zul; Sakinah, Maya; Syarif, Rini (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
Tax is one of the sources of state revenue that plays an important role in increasing development progress in Indonesia. Tax is also a mandatory contribution to the state owed by individuals or bodies that is mandatory based on the Law, without receiving direct compensation and is used for state needs for the greatest prosperity of the state. Without tax, most state activities cannot be carried out. The Directorate General of Taxes always strives to optimize services so that it is expected to increase public awareness and desire to be orderly as taxpayers, one of which is by carrying out tax reform, namely utilizing information and communication technology by implementing the E-Form system. The purpose of this review is to find out how the procedure for reporting the Annual Tax Return for entrepreneur taxpayers uses E-Form, and to find out what obstacles occur when reporting the Annual Tax Return for entrepreneur taxpayers using E-Form at the Bogor Pratama Tax Office. The procedure for reporting the Annual Tax Return for business taxpayers using E-Form at the Bogor Pratama Tax Office is in accordance with the procedures of the Directorate General of Taxes, but there are still many taxpayers who do not fully understand how to report the Annual Tax Return for business taxpayers using E-Form so that taxpayers come to the Bogor Pratama Tax Service Office. Keywords: Tax, E-Form, Procedure